2005
DOI: 10.1210/en.2004-0695
|View full text |Cite
|
Sign up to set email alerts
|

Ingested Medium-Chain Fatty Acids Are Directly Utilized for the Acyl Modification of Ghrelin

Abstract: Ghrelin, an acylated brain and gut peptide, is primarily produced by endocrine cells of the gastric mucosa for secretion into the circulation. The major active form of ghrelin is a 28-amino-acid peptide containing an n-octanoyl modification at serine that is essential for activity. Studies have identified multiple physiological functions for ghrelin, including GH release, appetite stimulation, and metabolic fuel preference. Until now, there has not been any report detailing the mechanism of ghrelin acyl modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
158
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(176 citation statements)
references
References 38 publications
11
158
2
5
Order By: Relevance
“…2). These findings are consistent with previous whole-animal data indicating that ghrelin secretion is dependent on an exogenous source of octanoate (25). It appears that the ghrelin-secreting cells cannot synthesize octanoate de novo, nor can they shorten longchain fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…2). These findings are consistent with previous whole-animal data indicating that ghrelin secretion is dependent on an exogenous source of octanoate (25). It appears that the ghrelin-secreting cells cannot synthesize octanoate de novo, nor can they shorten longchain fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…BMIs of these patients were comparable to those of normal Japanese female children (23). These findings support the hypothesis that octanoyl-CoA is a primary substrate for ghrelin, although medium-chain triglyceride dietary lipids are a direct source for ghrelin acylation (7,16,24). Moreover, GOAT is a membrane-bound molecule in the endoplasmic reticulum (ER).…”
Section: Discussionsupporting
confidence: 75%
“…The eluate was evaporated and separated by RP-HPLC. All HPLC fractions were quantified using RIAs for ghrelin (4,14,15,16). RIAs for a ghrelin C-terminal region (C-RIA) and a ghrelin N-terminal region (N-RIA) measure des-acyl ghrelin and octanoyl-ghrelin respectively (15).…”
Section: Reverse-phase Hplcmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors regulating ghrelin acylation have been largely unknown, although increased availability of the FFA has been proposed to enhance the hormone acylation in mice. 43 Interestingly, Yang et al 44 have recently identified a novel enzyme implicated in the n-octanoylation of ghrelin, namely GOAT (Ghelin O-Acyltransferase), that is expressed in the major ghrelin-secreting tissues, such as the stomach and intestine. It seems plausible that obesity influences the expression and/or activity of this acyltranferase, leading to elevated plasma concentrations of acylated ghrelin.…”
Section: Discussionmentioning
confidence: 99%